"Tattoo Characteristics and Testing for Body Dysmorphic Disorder: An Internet-based Self-questionnaire Survey of 4,809 Individuals with Tattoos" - Justyna Putek; Aleksandra Batycka-Baran; Jacek C. Szepietowski; Wojciech Baran (Medical Journals Sweden, 2024)
Tattoos have become very popular worldwide in recent years. The aim of this study was to analyse a group of people interested in having tattoos, and screen them for body image disturbances. This cross-sectional self-administered internet-based survey included 4,809 individuals interesting in having tattoos. The majority of the study population were female (79.1%). The survey was conducted using a self-created questionnaire and the Body Dysmorphic Disorder Questionnaire - Dermatology version. Most tattoos in the study group were located on the forearms and hands (28.1%). The most popular motifs were plants (17.5%) and animals (16.9%). Out of 4,809 individuals, 19.9% had problems with acceptance of some parts of their body and 9.8% were screened for body dysmorphic disorder with the Body Dysmorphic Disorder Questionnaire - Dermatology version. Four percent of individuals reported that tattoos helped to improve their own perception of the appearance of their body by distracting attention from the other problems. Limitations of this study include possible participant selection bias and the overrepresentation of women. In conclusion, clinicians may expect to see more patients with tattoos and, of these, approximately 10% may be screened for body dysmorphic disorder.